BRAZILIAN PERMANENT ORIENTEERING TRAINING CAMPS: THE PARTNERSHIP BETWEEN THE PUBLIC UNIVERSITY AND THE BRAZILIAN ARMY IN EDUCATION AND SPORT - FRIEDMANN, RAUL MARQUES PEREIRA; VEIGA, LUIS AUGUSTO KÖENIG; NEVES, EDUARDO BORBA; ZENTAI, LÁSZLÓ (Boletim de Ciências Geodésicas, 2012)
According to the International Orienteering Federation, Orienteering is a sport in which the athlete performs a route with controlling points in the shortest possible time aided by the compass and the map. It is also a valuable tool for teaching orienteering in its widest sense, cartography and land navigation for all kinds of fieldwork. When compared to other sports, orienteering requires large periods of time to prepare any kind of course, even the training ones. The Permanent Orienteering Training Camps are an option to facilitate teaching and learning of this sport and navigational skills. This article summarizes the history of the Brazilian permanent orienteering training camps and presents the partnership among the Federal University of Technology — Paraná (UTFPR — Universidade Tecnológica Federal do Paraná), the Brazilian Army and other institutions for the encouragement of this sport and its educational possibilities at regional and national levels. This paper also presents the criteria and solutions adopted for these facilities and their possibilities in competition, training, education and research.